Research on Dead Time Compensation of Cascaded High-voltage Inverter - LI Xinghe; JIN Xinhai; WANG Shuxian (Kongzhi Yu Xinxi Jishu)
Because of the particularity of high voltage inverter(HVI) topology and algorithm, the uniform dead time compensation should be considered from the main control PWM, instead of respective dead time compensation for each power unit. Therefore, it first introduced the topology structure of high-voltage inverter system and its power unit, and then mainly analyzed the different directions of current , switch states and the different connecting ways of neutral points. Based on the analysis of dead time on how to influence the individual power unit of cascaded high-voltage inverter under carrier phase shift modulation, all the units of high-voltage inverter were involved, and then a dead time compensation strategy was put forward. Finally, through the experiment on the high-voltage inverter, it verified the effectiveness of the dead time compensation strategy in open loop VF control and closed loop vector control.